(3GdLRFjI h GdcdjI Hjf GdfXQjI h GdJWHjbs - (3GdSjO eMeO GMeO(B, (3GdSQjJjs ((3GdGScfOQjI(B:s (3GdOGQ GdLGeYjI(B,s, 2011)
(3GdWdH h GdYQV h h eQhfJgeG h JhGRf GdShb h fXQjI GdefaYI GdMOjI h JhGRf GdShb , fXQjI GdShGA h JWHjbGJ Ydi JhGRf GdeSJgdc , fXQjI GdGfJGL h JcGdjag h GdSdhc GdGbJUGOj ddhMOI GdGfJGLjI h CTcGd GdShb h JhGRf GdhMOI GdGfJGLjI , GdJhGRf GdYGe h GbJUGOjGJ GdhaGgjI , GdfehPL GdcdGSjcj h GdfehPL GdcjfRjs
Keywords: (3GdEbJUGO GdLRFjs; (3GdEbJUGO Gdcdjs; (3GdEbJUGO(B- (3fXQjGJs